Hubungan Model Pembelajaran Cooperative Learning Tipe Jigsaw dengan Hasil Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam Kelas XI di MAN 2 Kota Bogor - Himayati, Kisti; Fahmi Irfani; Khaidir Fadil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of the jigsaw cooperative learning model, student learning outcomes, and the relationship between the jigsaw model and learning outcomes in the subject of Islamic Cultural History (SKI). The study employed a quantitative approach using a correlational method involving 37 students in class XI-3 at MAN 2 in Bogor City. Data were collected through observation and achievement tests. The results indicate that the implementation of the jigsaw model falls into the “good” category with a percentage of 73.50%, student learning outcomes are in the “good” category with an average of 76.47, and there is a positive and significant relationship between the jigsaw model and student learning outcomes (r = 0.883; Sig. = 0.000). The better the implementation of the jigsaw model, the higher the students’ learning outcomes.